High-performance asymmetric supercapacitor based on graphene hydrogel-nickel composite and manganese (II) oxide-nickel hybrid - Chow, Jian You (2014)
Supercapacitors have emerged with the potential to enable major advances in energy storage. Literatures have shown that they have a number of important features including fast charging/discharging rate, excellent cycle stability, long shelf live and are environmentally friendly. As a result, supercapacitors may become an attractive power solution for an increasing number of applications. In this report, the performance of a type of supercapacitor, hydrid (asymmetric) capacitor will be evaluated. In theory by utilizing two different composite materials in each electrode, namely the Graphene Hydrogel - Nickel Foam (GH-NF) as the negative electrode and Manganese Dioxide-Nickel Foam ( MnO2-NF) as the positive electrode, the hybrid supercapacitor with an asymmetric electrode configuration will be able capitalise on both electrode materials' advantages in improving overall cell voltage, energy and power densities.